Protecting and Promoting Children’s Education Rights - Aáry-Tamás , Lajos (Pázmány Law Review, 2023)
The right to Education in Hungary is declared by the constitution (Fundamental Law). Act on National Public Education sets the general rules and legal circumstances of the rights and obligations about education in Hungary. The Commissioner for Educational Rights, established by this act, in one of the key defender of education rights. This article summarises the Commissioner’s experience and views on how the case law could develop the legal environment of education. Moreover it underlines the need for an open discussion on the aim of education.